Oxytocin receptor gene loss influences expression of the oxytocin gene in C57BL/6j mice in a sex- and age-dependent manner - Vaidyanathan, Radhika (J Neuroendocrinol, 2020)
Parental care and sensory stimulation are critical environmental factors that influence oxytocin (OXT) and its receptor (OXTR). Because developmental Oxt mRNA expression is enhanced by sensory-rich early life experience, and reduced by sensory deprivation, we predicted that compared to wild-type (WT) littermates, mice with congenital loss of OXTR (OXTR KO), as a genetically-induced deprivation, would show impaired Oxt mRNA expression in the offspring hypothalamus during development. Oxt mRNA levels of male and female OXTR KO mice were not different from WT littermates from P0-P6, but that by P8, OXTR KO showed significantly decreased Oxt mRNA expression in the hypothalamus compared to WT littermates. At P14, male and female OXTR KO mice had significantly decreased Oxt mRNA expression specifically in the paraventricular nucleus (PVN), but not the supraoptic nucleus (SON), compared to WT littermates. We assessed if this effect persisted in adulthood (P90) and found a significant genotype by sex interaction where male OXTR KO mice displayed a reduction in Oxt expression specific to the PVN compared to male WT littermates. In contrast, male and female OXTR KO adults had increased Oxt mRNA levels in the SON. These findings suggest that OXTR plays a role in developmental Oxt mRNA expression with sex by genotype interactions apparent at adulthood. We then measured OXT and neural activation in the PVN and SON at P14. We observed more OXT immunoreactive cells in the PVN of OXTR KO mice, but significantly fewer c-Fos immunoreactive cells. There were no genotype differences in immunoreactivity for OXT and no c-Fos activity in the SON at P14. Combined, these data suggest that OXTR WT P14 mice have more PVN activity and are more likely to release OXT than OXTR KO mice. Future experiments are warranted to understand which OXTR-expressing neural circuits modulate the development of the PVN oxytocin system.